Broadcasting as public service: a juridical analysis of the proposed rules on local content must-carry obligations in Brazil - Lira, Laura Fernandes de Lima (Law, State and Telecommunications Review, 2010)
Modern life is largely influenced by broadcast services in Brazil, with special attention to commercial television. Policy makers face a constant dilemma over how to rule this sector without damaging the right of speech. To deal with this issue it is necessary to study these services’ juridical nature and the consequences of its definition. This essay gives a panoramic view of broadcast services’ juridical nature as stated in the 1998 Constitution and also analyzes the limits between regulating these activities and restraining the liberty of speech. These concepts will be then applied to the Brazilian juridical framework with emphasis on the imposition of required percentages of national content at the distribution layer. The concept of public service and the limitation that it imposes upon electronic mass communication service providers, the normative tools of content control and the outcomes of new legislation pertaining content control and other regulatory issues are then analyzed. The conclusion is that the juridical principles related to the broadcast services have not being reflected into concrete benefits towards national content production, although some improvement can be achieved with the expected approval of the Proposition 29 (PL 29) by the Brazilian Congress in 2010.